Analisis Semiotika Charles Sander Peirce dalam Novel Kado Terbaik Karya J.S Khairen - Shefira Nurulita; Sri Rahayu (UIR Press, 2023)
The focus of the problem in this research is the semiotic study of the icon, index, and symbol aspects in the Best Gift Novel by J.S Khairen. This research belongs to the type of library research with a qualitative approach using descriptive methods. The data of this research is obtained from the quotes, narratives, monologues, and dialogues of the characters in the novel Kado Best by J.S Khairen which contains the semiotic aspects of icons, indexes and symbols. The results of data analysis in this study, namely first, the icon aspects contained in the novel Kado Best by J.S Khairen showed a relationship between the signs in the reference that were similar or scientific in nature. The icon aspect is marked on the character “I” as a marker referring to the character Rizki; second, the semiotics of the index aspect contained in the novel Kado Best by J.S Khairen shows a causal relationship (cause and effect) between the signifier and the signified. The data is dominant in statements that describe the actions and behavior of the characters described in the novel Kado Best, such as the actions of the characters who have causes and effects, either naturally or by violence; and third, the semiotics of the symbol aspects contained in J.S Khairen's novel Best Gifts are convention, the symbolic aspects of J.S Khairen's Best Gifts novels are related to everyday human life. Data on the symbol aspect in the novel Kado Best by J.S Khairen refers to symbols of affection which are depicted through expressions, body gestures, objects, and religion